The Crisis of Managerial Information Flows in Education: Theoretical Aspects and Social Realities - A. M. Osipov (Высшее образование в России)
The article considers theoretical aspects for the study and understanding of contemporary educational policies with the application of the concepts of bureaucracy. It also presents the results of an interregional study of information flows in the Russian education system. The redundancy, intensity and formalization of these flows constitute one of the painful aspects of work in this sphere, along with unfairly low wages. The article analyzes the materials of extensive sample surveys and the timing of the loads of the main job groups in the education system, data on document flow in institutions of various types and levels, and expert assessments in the three regions of the country. The amount and structure of information flows and paper work lead to institutional dysfunctions, they serve as a means for administrative pressure and imitation of manageability in education system. The article considers their impact on the social and professional well-being of educators. The author concludes that the main source of paper pressure and paper genocide in the education system is a management strategy that ignores the public mission of education and its multifaceted social effectiveness. This strategy expresses distrust of educators, contains ignorance towards public-state governance and has become a dead end for the Russian education system, a major obstacle to maintaining its potential, development and progress in view of growing global competition.